Homonymous Visual Field Defects - Skorkovská, Karolína (Springer International Publishing : Imprint: Springer, 2017)
This book provides a concise and up-to-date overview on homonymous visual field defects, with the focus especially on homonymous hemianopia. All aspects of the subject are covered, from anatomy and pathophysiology to diagnosis and management. Emphasis is placed on practical issues and major advances in ophthalmology, neurology, imaging techniques, and psychology. Rehabilitation strategies are described, and methods supporting compensation strategies are recommended. A separate chapter considers driving with homonymous hemianopia, which represents one of the critical issues in traffic ophthalmology. Homonymous Visual Field Defects will be of particular value to ophthalmologists, neurologists, neurosurgeons, and neuroscientists. It will be an invaluable asset in diagnostic and treatment decision making in patients with such defects, which occur primarily as a result of stroke, trauma, or tumor, cause reading and orientation disorders, and are the most frequent type of visual field deficit after acquired unilateral postchiasmal brain damage.
Keywords: Medicine.; Neurology.; Neurosurgery.; Ophthalmology.; elektronické knihy; electronic books